Critical specific work of flow for shear‐induced formation of crystal nuclei in poly (l‐lactic acid). Issue 4 (20th May 2019) - Iqbal, Naeem; Jariyavidyanont, Katalee; Rhoades, Alicyn M.; Androsch, René
ABSTRACT: Shear‐induced formation of crystal nuclei in the poly (l ‐lactic acid) homopolymer was analyzed by shearing the supercooled melt in a plate‐plate rheometer followed by evaluation of the kinetics of isothermal crystallization via viscosity measurements. The data revealed that shearing the melt for 10 seconds at 135°C and 140°C causes shear‐induced formation of nuclei if the shear rate is higher than about 0.1 s −1 . If the shear rate at these conditions is higher than about 1 s −1 then row‐nuclei, as detected by aligned spherulites, develop. Besides providing comprehensive data about the effects of rate and time of shear at 135°C and 140°C on the crystallization kinetics, the concept of specific work of flow was tested. Shear rate and time compensate each other to drive shear‐induced nuclei formation, and the critical specific work required to form shear‐induced crystal nuclei is around 20 to 50 kPa. Further conceptual work included the analysis of the microstructure along the radius of the sheared discs as it permits evaluation of the effect of a broad range of shear rates in a single experiment. Abstract : Subjecting the melt of the poly (l ‐lactic acid) homopolymer to a specific work of flow higher than 20 to 50 kPa permits shear‐induced formation of crystal nuclei. The concept of specific work of flow seems valid as shear rate and time can compensate each other to enforce shear‐induced nuclei formation. Analysis of the microstructure along the radius of the sheared discs permits evaluation of the effect of a broad range of shear rates in a single experiment.